Human capital and performance of small & medium manufacturing enterprises: a study of Pakistan / Muhammad Shujaat Mubarik - Muhammad Shujaat, Mubarik (2015)

(untitled)
The study focuses on the role of human capital (HC) and performance of small and medium enterprises (SMEs) in the manufacturing sector of Pakistan. Pakistan has adopted a ‘one-size-fits-all’ policy to address HC development in SMEs. This has however not brought any difference to the development state of the SMEs, as most of these firms have not been able to survive beyond the first-year of their inception. In this context, this study focused on the role of HC (based on the dimensions and sub-dimensions of HC) on the performance of SMEs in the manufacturing sector of Pakistan. The principal objectives of the study are summarized herein: First, the study derives the human capital index (HCI), accounting for various dimensions and sub-dimensions of HC. Second, the study tests for the differences in levels of HC by industry, size (small and medium) and ownership (foreign and local). Third, the study examines the direct and indirect links between HC and its dimensions, with five vectors of firm performance, namely productivity, export, innovation, technological progress, and survivability of firms. For developing the HCI, the study adopts a three-stage approach. First, appropriate dimensions and sub-dimensions of HC are identified from the literature. In the second stage, 9 dimensions and 35 sub-dimensions of HC are selected through an expert survey of various stakeholders related to SME development in Pakistan. By applying the Analytic Hierarchy Procedure (AHP), those selected dimensions and sub-dimensions of HC are prioritized to form the HCI. Based on this prioritization, the study develops a close-ended questionnaire to collect data on HC and firm performance from 750 manufacturing sector SMEs in Pakistan. The one-way analysis of variance (ANOVA), multivariate analysis of variance (MANOVA), and t-tests are applied to examine the differences in the levels of HC across SMEs, by industry, size, and ownership. Subsequently, the structural equation modeling (SEM) is used to investigate the direct and iv indirect (through absorptive capacity) effects of HC on productivity, export, innovation, technological progress, and survivability of firms. The core findings of the study are summarized below. First, the relative prioritization among the HC dimensions rank education at the top, followed by experience, skills, personal abilities, training, employee stability , attitude , health and compliance. Second, the results on the inter-industry differences in HC indicate that HC is highest in textiles, and lowest in furniture and sports industries. Further, the results show that the levels of HC differ by size and ownership. The analysis reveals that the levels of HC are significantly higher in medium firms relative to small firms; and in foreign firms relative to local firms. Finally, the results reveal the significant positive impact of HC on firm performance. Absorptive capacity is also found to mediate the relationship between HC and the five-performance cords of firms’. From the in-depth analysis of the different sub-dimensions of HC, the study concludes that different sub-dimensions of HC are important for different cords of firm performance, and for understanding the channels of those impacts, direct or indirect. Therefore, the study suggests that HC is important for firm performance. However, not all the sub-dimensions of HC are found to be important for overall firm performance. Therefore policy formulation at the macro and micro levels should take into account the sub-dimensions of HC, and not just the HC dimensions on aggregate